Cholesterol-Rich Lipid Rafts as Platforms for SARS-CoV-2 Entry - Palacios-Rápalo, Selvin Noé; De Jesús-González, Luis Adrián; Cordero-Rivera, Carlos Daniel; Farfan-Morales, Carlos Noe; Osuna-Ramos, Juan Fidel; Martínez-Mier, Gustavo; Quistián-Galván, Judith; Muñoz-Pérez, Armando; Bernal-Dolores, Víctor; del Ángel, Rosa María; Reyes-Ruiz, José Manuel (Frontiers in Immunology, 2021)
Since its appearance, the Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2), the causal agent of Coronavirus Disease 2019 (COVID-19), represents a global problem for human health that involves the host lipid homeostasis. Regarding, lipid rafts are functional membrane microdomains with highly and tightly packed lipid molecules. These regions enriched in sphingolipids and cholesterol recruit and concentrate several receptors and molecules involved in pathogen recognition and cellular signaling. Cholesterol-rich lipid rafts have multiple functions for viral replication; however, their role in SARS-CoV-2 infection remains unclear. In this review, we discussed the novel evidence on the cholesterol-rich lipid rafts as a platform for SARS-CoV-2 entry, where receptors such as the angiotensin-converting enzyme-2 (ACE-2), heparan sulfate proteoglycans (HSPGs), human Toll-like receptors (TLRs), transmembrane serine proteases (TMPRSS), CD-147 and HDL-scavenger receptor B type 1 (SR-B1) are recruited for their interaction with the viral spike protein. FDA-approved drugs such as statins, metformin, hydroxychloroquine, and cyclodextrins (methyl-β-cyclodextrin) can disrupt cholesterol-rich lipid rafts to regulate key molecules in the immune signaling pathways triggered by SARS-CoV-2 infection. Taken together, better knowledge on cholesterol-rich lipid rafts in the SARS-CoV-2-host interactions will provide valuable insights into pathogenesis and the identification of novel therapeutic targets.